(untitled) (Academicia Globe: Inderscience Research, 2026)
This article examines the role of artificial intelligence (AI) technologies in improving mechanisms for attracting investments in human capital and enhancing their effectiveness. The study analyzes theoretical approaches such as the Resource-Based View and Dynamic Capabilities Theory, emphasizing the strategic importance of human capital in the digital economy. Particular attention is given to the integration of AI technologies including machine learning, predictive analytics, natural language processing, generative AI, big data analytics, and reinforcement learning into human capital management systems. Empirical evidence shows that AI significantly increases the return on investment (ROI), improves workforce productivity, and enhances talent retention.